Isolation of Leptospira biflexa from bovine urine - Bahaman, Abdul Rani; Ibrahim, A. L. (Persatuan Doktor Veterinar Malaysia, 1985)
Leptospirosis is a major disease of most mammals caused by pathogenic leptospires from the Leptospira interrogans group which currently consists of 19 serogroups and more than 200 serovars. Saprophytic leptospires are just as numerous and are classified in Leptospira biflexa (Bergey, 1984)